New York live arts, A - Burger, Emily; Gibbons, Molly; Liberman, Katie; Oster, Sharon M. ([London] : SAGE, 2016)
In spring 2010, Jean Davidson, Executive Director of Foundation for Dance Promotion, Inc. d/b/a the Bill T. Jones/Arnie Zane Dance Company (BTJ), leaned back in her chair in her Harlem office and looked at the financial models one more time. The numbers seemed to indicate that merging BTJ with Dance Theater Workshop (DTW) made sense, but this was uncharted territory. BTJ was primarily a dance performance company, and DTW was primarily a performance space presenting innovative programs. If BTJ went through with a full merger with DTW, it would be unprecedented. No mergers had occurred at this scale in New York's dance world before. But other forms of partnership, which would be less risky, would likely yield smaller returns. This case study analyses this topic.
Originally Published in: Burger, E., Gibbons, M., Liberman, K., & Oster, S. (2014). New York Live Arts: A. 14-013. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Bill T. Jones/Arnie Zane and Company; Strategic alliances (Business) -- Case studies; Consolidation and merger of corporations -- Case studies